Recent technological trends in management and library system : issues and challenges - Kumar, Rajesh (New Delhi : Wisdom Publications, 2008)
Proceedings of the National Conference on Recent Technological Trends in Management and Library System : Issues and Challenges, held at New Delhi during 4-5 January 2008.
Gifted by VCO, IGNOU
Keywords: Libraries -- Information technology -- Congresses; Digital libraries -- India -- Congresses; Management -- Congresses -- India; Conference papers and proceedings; Congresses